A case report of early onset intrahepatic cholestasis of pregnancy. (18th April 2012) - Edoo, AWI; Imcha, M; Ali, A; Burke, G; Cotter, A; Skehan, M
Abstract : Background: Obstetric cholestasis is a disorder of unknown aetiology which typically presents in pregnancy after 30weeks gestation. Few cases have been diagnosed in the first trimester. Case report: A 27 years old primigravida presented at 13 weeks gestation with intense pruritus all over the body. She had a history of a cholecystectomy and both she and her sister had experienced pruritus when using the combine oral contraceptive pill. At 13weeks her bile salt level was 53umol/L (0-14umol/L) with both ALT and GGT elevated three fold. An extensive hepatic work up outruled any other liver pathology. At 17weeks with a bile salt level of 199umol/L, the diagnosis of intrahepatic cholestasis of pregnancy was confirmed. Both her symptoms and liver biochemistry responded to treatment with ursodeoxycholic acid with bile salt declining to < 2umol/L at 24 weeks albeit temporarily. Weekly fetal surveillance was performed from 26weeks gestation. She underwent induction of labour at 36 weeks for preterm prelabour rupture of membranes and delivered a live male infant in excellent condition weighing 2.7kgs. Ursodeoxycholic acid was discontinued postpartum with normalisation of liver biochemistry within three weeks. Conclusion: Pruritus in the first trimester although rare should be taken seriously and include a work up for OC in order to achieve an optimal pregnancy outcome especially as it is unknown if early occurrence is associated with higher bile acid levels in pregnancy and if the impact of prolonged exposure to bile acids in pregnancy is associated with a higher risk of perinatal morbidity and mortality.